Thematic analysis of disinformation in the Communication and Information area: a study based on the Brazilian Digital Library of Theses and Dissertations (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
This work is a part of the Master's research, in progress, which has as its central point, the theme "disinformation". The research aims to analyze the subthemes related to disinformation through the analysis of works indexed in the Brazilian Digital Library of Theses and Dissertations, between 2020 and 2022. In the methodological scope, it is characterized as an exploratory study with a quantitative and qualitative approach . Partial results indicate a growing interest in the topic from 2020 onwards, showing its relevance and the need to continue research through the investigation of related themes with which disinformation has been discussed.
Keywords: thematic analysis; misinformation; subtopics; Brazilian Digital Library of Theses and Dissertations